Interaction mechanism of thiol functional sites on magnetic molecularly imprinted polymer towards perfluorooctanoic acid in aqueous solution - Loshiny, Nageshwaran (2025)
This project focused on the synthesis and characterization of magnetic molecularly imprinted polymers (MMIPs) and molecularly imprinted polymers (MIPs) for selective perfluorooctanoic acid (PFOA) adsorption. Magnetic molecularly imprinted polymers (MMIPs) and molecularly imprinted polymers (MIPs) were synthesized to selectively adsorb perfluorooctanoic acid (PFOA) from aqueous solutions. The synthesis involved Fe₃O₄ nanoparticles for magnetic properties and allylthiourea (AT) as the functional monomer, with ethylene glycol dimethacrylate (EGDMA) as the crosslinker. Characterization techniques such as SEM-EDX and FTIR confirmed the successful incorporation of functional groups, magnetic particles, and specific binding sites for PFOA. SEM images revealed porous structures in MIP and MMIP, facilitating selective binding, while EDX confirmed the presence of essential elements, including iron (Fe) in the magnetic variants. The FTIR spectrum displayed characteristic peaks for thiol, ester, and C=S groups, along with C-F stretching vibrations, indicating successful imprinting of PFOA. MMIPs demonstrated high practicality due to their magnetic properties, enabling easy recovery and reusability in environmental applications. The absence of fluorine signals in the EDX spectra was attributed to fluorine encapsulation within the polymer matrix or desorption during sample preparation. Nonetheless, the structural and functional integrity of the polymers remained intact. This study highlights the effectiveness of molecular imprinting in producing selective adsorption materials and emphasizes the role of silica-coated magnetic nanoparticles in enhancing polymer stability and functionality. Future recommendations include exploring advanced characterization techniques such as XPS and NMR, optimizing polymerization conditions, and evaluating the reusability and scalability of these polymers for large-scale water remediation applications.